2020
DOI: 10.1093/nar/gkaa636
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly family protein MCPH1 stabilizes RAD51 filaments

Abstract: Microcephalin 1 (MCPH1) was identified from genetic mutations in patients with primary autosomal recessive microcephaly. In response to DNA double-strand breaks (DSBs), MCPH1 forms damage-induced foci and recruits BRCA2–RAD51 complex, a key component of the DSB repair machinery for homologous recombination (HR), to damage sites. Accordingly, the efficiency of HR is significantly attenuated upon depletion of MCPH1. The biochemical characteristics of MCPH1 and its functional interaction with the HR machinery had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Previous work has suggested that full-length MCPH1 binds to DNA and chromatin ( Chang et al, 2020 ; Yamashita et al, 2011 ) so we tested whether MBP-MCPH1 1-435 and MBP-MCPH1 196-435 are able to bind to a 50 bp sequence of dsDNA using electrophoretic mobility shift assay (EMSA). Both MCPH1 1-435 -MBP and MCPH1 196-435 -MBP were able to induce a shift, however higher concentrations of MCPH1 196-435 MBP were required for a complete shift in the free DNA band, suggesting MCPH1 1-195 MBP could have a role in DNA binding ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested that full-length MCPH1 binds to DNA and chromatin ( Chang et al, 2020 ; Yamashita et al, 2011 ) so we tested whether MBP-MCPH1 1-435 and MBP-MCPH1 196-435 are able to bind to a 50 bp sequence of dsDNA using electrophoretic mobility shift assay (EMSA). Both MCPH1 1-435 -MBP and MCPH1 196-435 -MBP were able to induce a shift, however higher concentrations of MCPH1 196-435 MBP were required for a complete shift in the free DNA band, suggesting MCPH1 1-195 MBP could have a role in DNA binding ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…Binding of MCPH1’s C-terminal BRCT domains to phosphorylated histone H2AX ( Venkatesh and Suresh, 2014 ) is thought to play a part in the DNA damage response, while the premature chromosome condensation caused by mutations within its N-terminal BRCT has been attributed to this domain’s defective association with the SWI/SNF nucleosome remodelling complex and SET1 ( Leung et al, 2011 ). MCPH1 is also thought to bind DNA and has been proposed to function in telomere maintenance, centriole organisation and CHK1 activation ( Alderton et al, 2006 ; Chang et al, 2020 ; Cicconi et al, 2020 ; Gruber et al, 2011 ; Lin and Elledge, 2003 ). In contradiction to the finding that MCPH1 binds directly to condensin II, it is widely believed that the N-terminal ~200 residues of MCPH1 compete with condensin II for chromosomal binding ( Yamashita et al, 2011 ), in other words, MCPH1 has been proposed to occupy loci required for condensin II’s chromosomal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, MCPH1 interacts with the transcription factor E2F1 and promote its loading on the promoter of BRCA1 to increase the BRCA1 expression ( Yang et al., 2008 ). Last, it has been reported that MCPH1 helps localization of BRCA2 to sites of DSBs and enhances the stability of RAD51-ssDNA filaments, both of which are key players in HR repair ( Wu et al., 2009 ; Chang et al., 2020 ). Thus, ASPM and MCPH1 regulate BRCA1 levels at post-translational stage and transcriptional stage, respectively, in HR repair.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that full length MCPH1 binds to DNA and chromatin 33,42 so we tested whether MBP-MCPH11-435 and MBP-MCPH1196-435 are able to bind to a 50 bp sequence of dsDNA using electrophoretic mobility shift assay (EMSA). Both MCPH11-435-MBP and MCPH1196-435-MBP were able to induce a shift, however higher concentrations of MCPH1196-435 MBP were required for a complete shift in the free DNA band, suggesting MCPH11-195 MBP could have a role in DNA binding (Figure 7B).…”
Section: Mcph1 Does Not Alter Condensin II Atpase Activity or Dna Binding In Vitromentioning
confidence: 99%
“…Binding of MCPH1's C-terminal BRCT domains to phosphorylated histone H2AX 36 is thought to play a part in the DNA damage response, while the premature chromosome condensation caused by mutations within its N-terminal BRCT has been attributed to this domain's defective association with the SWI/SNF nucleosome remodelling complex and SET1 37 . MCPH1 is also thought to bind DNA and has been proposed to function in telomere maintenance, centriole organisation and CHK1 activation [38][39][40][41][42] . In contradiction to the finding that MCPH1 binds directly to condensin II, it is widely believed that the N-terminal ~200 residues of MCPH1 compete with condensin II for chromosomal binding 33 , in other words, MCPH1 has been proposed to occupy loci required for condensin II's chromosomal activity.…”
Section: Introductionmentioning
confidence: 99%